Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (SLACK Inc., 2000)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Strategies for enhancing student learning by managing ambiguities in clinical settings. - Taylor, P.A. (Nurse educator, 2000)
Have you ever watched as care providers, be they student nurses or staff nurses, display behaviors that seem to indicate that they are becoming overwhelmed by situations in the acute care setting? Have you also observed other providers who seem to thrive on the "challenges" presented by these same situations? The same situation stimulates responses that reflect opposite ends of a continuum, the continuum of tolerance of ambiguity. The nurse educator needs to develop a greater understanding of the elements in the clinical situation (the ambiguities) that have stimulated the behavioral responses, and how an individual's level of tolerance of ambiguity influences reactions to the ambiguous situations. These understandings provide the nurse educator with the foundation for developing teaching strategies to facilitate effective management of ambiguous situations in clinical settings.
5 citations (Crossref) [2023-10-31]
Keywords: *Burnout; Professional/pc [Prevention & Control]; *Education; Nursing/mt [Methods]; *Nurses/px [Psychology]; *Teaching/mt [Methods]; Burnout; Professional; Education; Nursing; Humans; Nurses; Nursing Process; Teaching; article; burnout; dept.nur; human; methodology; nurse; nursing education; nursing process; psychological aspect; teaching